Analise de indicadores fundamentalistas para avaliar valor da empresa: estudo de caso Petrobrás - Silva, Leandro Farias da (Universidade do Vale do Rio dos Sinos, 2010)
This stuff has the main target the evaluation by fundamentalist approach the investor’s value growing evolution. The use of available data that properly handled can provide subsidies to the investors to make decisions about stocks investments. The Fundamentalist Analysis applied to the recent past of the company is able to decrease the uncertainties about the stocks’ future movements. Constitutes in clarify the main facts related to the company’s profitability based on indicators. The result of this survey applied in this study showed that is possible to measure company’s value through the combination of indicators obtaining the just stock prize, helping investor in finding the right time of investment decision.
Keywords: Análise fundamentalista; Indicadores; Rentabilidade; Investidores; Fundamentalist analysis; Indicators; Profitability; Investors